2018
DOI: 10.1037/pri0000063
|View full text |Cite
|
Sign up to set email alerts
|

Decision making and the use of evidence-based practice: Is the three-legged stool balanced?

Abstract: This article presents the results of a qualitative analysis of interviews with 25 psychologists in independent practice, with a focus on decision making with a selected patient. We endeavored to examine how clinical decision making intersected with the principles of evidence based practice (EBP) as laid out by Spring (2007). Clinicians reported that diagnostic impressions were generally formulated through unstructured assessment rather than validated instruments, and that treatment selection was based on thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
(60 reference statements)
0
19
0
3
Order By: Relevance
“…EBPI implementation is particularly challenging because most people receive treatment for mental illness in nontraditional or integrated settings such as primary care [12] and schools [13,14]. EBPIs were typically not developed for these settings, resulting in poor contextual fit and low adoption [15,16]. To address EBPI implementation barriers, decades of research has focused on provider, patient, setting, and policy barriers [17], yet actionable and cost-efficient solutions remain elusive [18].…”
Section: Introductionmentioning
confidence: 99%
“…EBPI implementation is particularly challenging because most people receive treatment for mental illness in nontraditional or integrated settings such as primary care [12] and schools [13,14]. EBPIs were typically not developed for these settings, resulting in poor contextual fit and low adoption [15,16]. To address EBPI implementation barriers, decades of research has focused on provider, patient, setting, and policy barriers [17], yet actionable and cost-efficient solutions remain elusive [18].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted among twenty-five clinical psychologists revealed that "diagnostic impressions were generally formulated through unstructured assessment rather than validated instruments, and that treatment selection was based on therapists' perceptions of a treatment's match with client characteristics." 44 Likewise, numerous studies have demonstrated that there may be an industry-wide preference for clinical expertise among clinicians when making treatment choices and discounting the contribution of other sources of evidence. 45 The same can be true in the process of making ministry decisions.…”
Section: Problem #3: Biasmentioning
confidence: 99%
“…Furthermore, research outcomes are mostly disseminated in scientific journals, meaning that results may not reach applied professionals (Echeburúa et al, 2010). Therefore, clinical decisions are made based on their professional experience (Gyani, Sharan, Myles, & Rose 2014; Safran et al, 2011; Stewart & Chambless, 2007;Stewart, Chambless, & Stirman, 2018;Stewart et al, 2012). Likewise, prior studies have revealed that personal factors such as age, therapeutic orientation, education level, years of experience, and professional context, impact on the use of EBTs.…”
Section: Extended Summarymentioning
confidence: 99%
“…El hecho de que los resultados de la investigación se divulguen mayoritariamente en revistas científicas puede ocasionar que dichos resultados no lleguen a los profesionales aplicados (Echeburúa et al, 2010). Varias encuestas han demostrado que pocos profesionales de la psicología clínica leen revistas científicas (Safran, Abreu, Ogilvie y DeMaria, 2011;Stewart y Chambless, 2007), tomando las decisiones de tratamiento en base a su experiencia clínica o a la de sus compañeros (Gyani, Shafran, Myles, y Rose 2014;Safran et al, 2011;Stewart y Chambless, 2007;Stewart, Chambless y Stirman, 2018;Stewart et al, 2012). Además, algunos estudios han señalado que factores personales como la edad del profesional (Aarons y Sawizky, 2006), la orientación terapéutica (Gyani et al, 2014;Safran et al, 2011;Stewart y Chambless, 2007), el nivel educativo (Beidas y Kendall, 2010), los años de experiencia clínica (Beidas y Kendall, 2010) y el ámbito laboral (Gyani et al, 2014) pueden influir en el uso de los TBE.…”
unclassified